Effect of Clinical Pathology Course on Attitude and Learning in Medical Students Taking Clinical Laboratory Course in Kerman University of Medical Sciences - Elham Jafari; Shariar Dabiri; Foroogh Mangeli; Reza Baneshi (Kerman University of Medical Sciences, 2019)
Background According to the importance of the clinical pathology for diagnosis, decision making regarding preventive and minimally invasive methods, and treatment follow-ups, it is useful to familiarize medical students with better utilization of laboratory tests before clinical practice and incorporate them into the curriculum. Objectives The current study aimed at investigating the quality of education and satisfaction with clinical pathology course among medical students at physiopathology level initiated since 2014 at Kerman University of Medical Sciences for further systematization of the curriculum, and its efficacy in increasing students' knowledge. Methods In the current interventional study, medical students at physiopathology level were enrolled and, after making necessary coordination with the Deputy of Education, a one-unit clinical pathology course was added to routine (five-unit) physiopathology course for the students attending the second semester of 2013 - 2014 academic year. Two groups of students attending internship program including 42 subjects that took the clinical pathology course and 42 other ones that did not take the course were consecutively enrolled. A questionnaire was distributed among the subjects in the two groups and the obtained data were analyzed with SPSS version 19.0 using chi-square test. Results Overall, the medical students in both groups believed that clinical pathology course was essential for both theoretical and practical education. Most of the students in the two groups perceived that the inclusion of clinical pathology course in physiopathology course was good. Both groups perceived the course as useful for better management of patients in postgraduate studies. Conclusions There is no theoretical and applied academic course with rational systematic training objectives in the clinical pathology field for better utilization of laboratory tests. It highlights the need for paying further attention and planning in this field.